Change in alcohol consumption and risk of death from all causes and from ischaemic heart disease. Issue 6802 (7th September 1991) - Lazarus, N B; Kaplan, G A; Cohen, R D; Leu, D J
Abstract : OBJECTIVE–To examine the association between alcohol consumption and mortality from all causes and from ischaemic heart disease with a focus on differentiating between long term abstainers and more recent non-drinkers. DESIGN–Cohort study of changes in alcohol consumption from 1965 to 1974 and mortality from all causes and ischaemic heart disease during 1974-84. SETTING–Population based study of adult residents of Alameda County, California. SUBJECTS–2225 women and 1845 men aged 35 and over in 1965. MAIN OUTCOME MEASURES–Alcohol consumption in 1964 and 1974 and mortality from all causes and from ischaemic heart disease during 1974-84. RESULTS–There was a significantly higher risk of death from all causes and from ischaemic heart disease in women who gave up drinking between 1965 and 1974 than in women who continued to drink (relative risk 1.72, 95% confidence interval 1.11 to 2.66, and 2.75, 1.44 to 5.23, for all causes and ischaemic heart disease respectively). A significant increase in risk was not seen in men who gave up drinking (1.32, 0.87 to 2.01, and 0.95, 0.41 to 2.20, respectively). Among men, long term abstainers compared with drinkers were at increased risk of death from all causes and from ischaemic heart disease, though the associations were not significant (1.40, 0.98 to 2.00, and 1.40, 0.76 to 2.58, for all causes and ischaemic heart disease respectively). CONCLUSION–Some of the increased risk of death from all causes and from ischaemic heart disease associated with not drinking in women seems to be accounted for by higher risks among those who gave up drinking. Men who are long term abstainers may also be at an increased risk of death. The heterogeneity of the non-drinking group should be considered when comparisons are made with drinkers.